A Study of Navasandhi Nirtta and Sandhyavahana [An account of the Invocation of the Nine Gods who are Guardians of the Centre and the Other Eight Directions] - Balakailasanathasarma, M. (Eastern University, Sri Lanka, 2006)
This is a special invocation for the gods who are guardians of the centre and the eight directions in the temple or in the village. As referred to more than once this religious programme of Navasandhi Nirtta blending beautifully music and dance items is indeed quite interesting. In the case of all the nine directions the Saivagamas give specific names of tala, raga, dance movements etc required to be performed. Even here different Agamic texts are not always unanaechimous on these names. Navasandhi nirtta starts after the officiating priest recites a Curnika(Poetic text of Agama). This is followed by short performance of instrumentalists and Rudragamas. Such performances are set to particular raga and tala and in the case of dance the particular bhaba also has to be created besides the buddha the nirtta. All these must conform to the specific aspects of the particular guardian gods of the directions. A critical inter-disciplinary study of the Navasandhi Nirtta from the view points of religion ritualistic dance and musical details will be quite interesting and useful.